2020
DOI: 10.1093/rapstu/raaa009
|View full text |Cite
|
Sign up to set email alerts
|

How Does Household Spending Respond to an Epidemic? Consumption during the 2020 COVID-19 Pandemic

Abstract: Utilizing transaction-level financial data, we explore how household consumption responded to the onset of the COVID-19 pandemic. As case numbers grew and cities and states enacted shelter-in-place orders, Americans began to radically alter their typical spending across a number of major categories. In the first half of March 2020, individuals increased total spending by over 40% across a wide range of categories. This was followed by a decrease in overall spending of 25%–30% during the second half of March co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
302
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(379 citation statements)
references
References 25 publications
18
302
0
6
Order By: Relevance
“…Historically, the year 2020 will be remembered for the global battle against an invisible enemy. Since the emergence of the novel coronavirus (COVID- 19) in December 2019 in Wuhan, China, the world is experiencing unprecedented phenomena [1]. In March of this year, COVID-19 was declared a pandemic by the World Health Organization (WHO), and emergency measures have been internationally implemented as the outbreak continues to threaten public health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the year 2020 will be remembered for the global battle against an invisible enemy. Since the emergence of the novel coronavirus (COVID- 19) in December 2019 in Wuhan, China, the world is experiencing unprecedented phenomena [1]. In March of this year, COVID-19 was declared a pandemic by the World Health Organization (WHO), and emergency measures have been internationally implemented as the outbreak continues to threaten public health.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study captures the dissemination of COVID-19 information in relation to the outbreak progression from medical-oriented social media sources [17]. Other studies employing data-driven methodologies have also been introduced to estimate the negative impacts on various sectors such as the economy, public health, and human mobility [18][19][20][21][22][23]. In particular, mobility data have been identified as being especially relevant, and researchers have provided in-depth knowledge on how to leverage mobile device location data for analyzing propagation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the way people purchase and consume food has changed, with some consumers even resorting to panic buying to mitigate the risk of future shortages [22]. Consumers in the United States increased stockpiles of home goods, such as food, during COVID-19 [23]. However, an absence of panic buying and food stockpiling has been reported in Qatar [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are recent articles that make use of such information. In the United States, Baker et al ( 2020 ) use de-identified non-random data from a Fintech company at the transaction and individual level. They find a spike in total spending when cases begin to increase (late February and early March) but a subsequent decrease of close to 50 percent with respect to January and early February.…”
Section: Introductionmentioning
confidence: 99%